Clinical Outcomes of Transcranial and Endoscopic Endonasal Surgery for Craniopharyngiomas: A Single-Institution Experience - Nie, Chuansheng; Ye, Youfan; Wu, Jingnan; Zhao, Hongyang; Jiang, Xiaobing; Wang, Haijun (Frontiers in Oncology, 2022)
Abstract Objective: Craniopharyngioma has always been a challenge for the neurosurgeon and there is no consensus on optimal treatment. The object of this study was to compare surgical outcomes and complications between transcranial surgery (TCS) and endoscopic endonasal surgery (EES) of craniopharyngiomas Methods: A retrospective review of patients who underwent resection of craniopharyngiomas at Wuhan Union Hospital between January 2010 and December 2019 was performed. A total of 273 patients were enrolled in this retrospective study. All patients were analyzed with surgical effects, endocrinologic outcomes, complications, and follow-up results. Results: 185 patients underwent transcranial surgery and 88 underwent extended endoscopic endonasal surgery. Patient demographic data, preoperative symptoms, and tumor characteristics were similar between the two groups. The mean follow-up was 30.5 months (range 8-51months). The most encountered complications were endocrine deficits, cranial nerve injury, postoperative CSF leak, death, and others. The EES group had a greater gross total resection (GTR) rate (89.8% EES vs 77.3% TCS, p<0.05), lower rate of hypopituitarism (53.4% EES vs 68.1% TCS, p<0.05) and diabetes insipidus (DI) (51.1% EES vs 72.4% TCS, p<0.05). More Postoperative CSF leaks occurred in the EES group (4.5% EES vs 0% TCS, p<0.05). The incidence of cranial nerve injury was significantly higher in the craniotomy group (1.1% EES vs 7.6% TCS, p<0.05). More patients in the EES group with preoperative visual deficits experienced improvement after surgery (74.5% EES vs 56.3% TCS, p<0.05). There were statistical differences in the recurrence rates (12.5% EES vs 23.8% TCS, p<0.05) between the 2 groups. Conclusion: These data support the view that EES is a safe and effective minimally invasive surgery compared to craniotomy, providing a viable alternative resection with less neurological injury and lower recurrence rates.